Problematika Zakona o predlaganju kandidatov iz Slovenije za sodnike mednarodnih sodišč - Kramberger Mendek, Urška (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2022)
International courts and tribunals have gained importance with the obligation to use peaceful means of dispute settlement. Those means have become an important instrument of foreign policy, which has led to an increased efforts to have representatives elected to international courts and tribunals. States began to invest more resources in the election of their candidates, using various approaches and incentives. Concerns began to arise that the candidates perhaps were not elected only because of their competences, but also because of the influence of their state and successful lobbying. Therefore, the international community has begun to adopt several international standards of judicial independence, encouraged the creation of mechanisms to review the nominations of candidates for judges, and called on countries to nominate suitable candidates. Slovenia responded to such concerns very early on and adopted the Act on Nomination of Candidates from the Republic of Slovenia for Judges at International Courts, which regulates the national selection process of international judges and arbitrators. A comparison of the Act with the regulations and conditions specified in the statutes of individual international courts shows that the Act prescribes additional conditions and, with the required procedure, even limits the possibilities for the election of Slovenian candidates for judges in international courts and arbitrations, where Slovenia does not have a guaranteed position of a judge.
Keywords: arbitri; mednarodna kazenska sodišča; mednarodna sodišča; mednarodni sodniki; neodvisnost; Organizacija združenih narodov; volitve